Synthesis and Characterization of α-(Arylaminothiocarbonyloxy)hydrocarbylphosphonates - LI, JIANPING; ZHU, JUNGE; LIU, RUIJIE (Asian Journal of Chemistry, 2010)
In this study, twelve new α-(arylamino thiocarbonyloxy)- hydrocarbylphosphonates were synthesized in excellent yields by addition reaction of α-hydroxyhydrocarbylphosphonates with aryl isothiocyanates in the presence of sodium methoxide. Their structures have been confirmed by IR, 1H NMR and elemental analysis.